Multi-decadal river flow variations in France - J. Boé; F. Habets (Hydrology and Earth System Sciences, 2014)
In this article, multi-decadal variations in the French hydroclimate are investigated, with a specific focus on river flows. Based on long observed series, it is shown that river flows in France generally exhibit large multi-decadal variations in the instrumental period (defined in this study as the period from the late 19th century to the present), especially in spring. Differences of means between 21 yr periods of the 20th century as large as 40% are indeed found for many gauging stations. Multi-decadal spring river flow variations are associated with variations in spring precipitation and temperature. These multi-decadal variations in precipitation are themselves found to be driven by large-scale atmospheric circulation, more precisely by a multi-decadal oscillation in a sea level pressure dipole between western Europe and the eastern Atlantic. It is suggested that the Atlantic Multidecadal Variability, the main mode of multi-decadal variability in the North Atlantic–Europe sector, controls those variations in large-scale circulation and is therefore the main ultimate driver of multi-decadal variations in spring river flows. Potential multi-decadal variations in river flows in other seasons, and in particular summer, are also noted. As they are not associated with significant surface climate anomalies (i.e. temperature, precipitation) in summer, other mechanisms are investigated based on hydrological simulations. The impact of climate variations in spring on summer soil moisture, and the impact of soil moisture in summer on the runoff-to-precipitation ratio, could potentially play a role in multi-decadal summer river flow variations. The large amplitude of the multi-decadal variations in French river flows suggests that internal variability may play a very important role in the evolution of river flows during the next decades, potentially temporarily limiting, reversing or seriously aggravating the long-term impacts of anthropogenic climate change.